Electrochemical reduction method and catalyst
The electrochemical reduction method using a Ti-containing oxide catalyst with Cu enhances CH4 production selectivity and current density, addressing inefficiencies in existing CO2 conversion technologies.
Patent Information
- Application Number
- JP2023503881
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-02
- Filing Date
- 2022-03-02
- Publication Date
- 2024-12-23
- Estimated Expiration
- 2042-03-02
AI Technical Summary
Existing electrochemical reduction methods for converting CO2 into CH4 suffer from insufficient selectivity and current density, necessitating improvements in production efficiency.
An electrochemical reduction method using a catalyst containing a Ti-containing oxide with a band gap of 3 eV or less, combined with Cu, and specific XPS and UV-Vis spectral characteristics, is employed to enhance the selectivity and current density of CH4 production.
The method significantly improves the selectivity and current density of CH4 production, achieving high efficiency in converting CO2 to CH4.
Smart Images

Figure 0007604036000008 
Figure 0007604036000009 
Figure 0007604036000010
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrochemical reduction method. and catalyst Regarding. This application claims priority to U.S. Provisional Application No. US63 / 155,309, filed March 2, 2021, the contents of which are incorporated herein by reference. [Background technology]
[0002] The electrochemical reduction of CO2 (hereinafter sometimes referred to as ECO2R), which uses renewable electricity to produce fuels and chemical raw materials from CO2, is attracting attention not only as a low-carbon material synthesis process, but also as a new method of storing intermittent renewable energy such as solar and wind power.
[0003] For example, Non-Patent Document 1 discloses an electrochemical reduction method in which CO2 is reduced to CH4 using a CeO2 catalyst to which Cu is added. [Prior art documents] [Non-patent literature]
[0004] [Non-Patent Document 1] Yifei Wang, Zheng Chen, Peng Han, Yonghua Du, Zhengxiang Gu,Xin Xu, and Gengfeng Zheng, Single-Atomic Cu with Multiple Oxygen Vacancies on Ceria for Electrocatalytic CO2 Reduction to CH4, ACS Catalysis 2018, 8, 7113-7119. Summary of the Invention [Problem to be solved by the invention]
[0005] However, the selectivity of CH4 production and the rate of CH4 production (current density) were insufficient in the method of Non-Patent Document 1. Currently, there is a demand for an improvement in the selectivity of CH4 production and the current density compared to the method of Non-Patent Document 1.
[0006] The present invention has been made in consideration of the above circumstances, and provides an electrochemical reduction method that improves the selectivity of CH4 production in the electrochemical reduction reaction of CO2. and catalyst The purpose is to provide. [Means for solving the problem]
[0007] (1) In one embodiment of the present invention, a method for electrochemical reduction includes contacting a catalyst containing an oxide containing Ti with a solution having a pH of 5 to 15 and CO2, and electrochemically reducing the CO2. At least a part of the oxide containing Ti has a band gap of 3 eV or less. .
[0008] (2) The electrochemical reduction method according to (1) above, The CO2 may be electrochemically reduced to produce methane.
[0010] ( 3 )the above (1) or (2) In the electrochemical reduction method described in the above, the content of the oxide containing Ti in the catalyst may be 10 wt % or more.
[0011] ( 4 ) Above (1)~( 3 In the electrochemical reduction method described in any one of (1) to (5), the catalyst may contain Cu.
[0012] ( 5 )the above( 4 In the electrochemical reduction method described in ), an XPS spectrum of the catalyst measured by X-ray photoelectron spectroscopy (XPS) may have a peak between 931 eV and 933 eV, and the half width of the peak between 931 eV and 933 eV may be 1.4 eV to 1.9 eV.
[0013] ( 6 )the above( 5In the electrochemical reduction method described in ), the Cu content of the catalyst may be 0.001 wt % to 90 wt %.
[0014] ( 7 ) Above (1)~( 6 In the electrochemical reduction method described in any one of the above, the oxide containing Ti may be TiO2.
[0015] ( 8 ) Above (1)~( 7 In the electrochemical reduction method according to any one of the above, in the ultraviolet-visible absorption spectrum of the catalyst, an intensity I 400 and the intensity I at wavelength 600 nm 600 Comparison with I 400 / I 600 may be 0.5 to 3.
[0016] ( 9 ) Above (1)~( 8 In the electrochemical reduction method according to any one of the above items 1 to 5, in an XPS spectrum of the catalyst measured by X-ray photoelectron spectroscopy (XPS), there may be a peak between 528 eV and 532 eV, and the half width of the peak between 528 eV and 532 eV may be 1.2 eV to 1.55 eV.
[0017] ( 10 ) Above (1)~( 9 In the electrochemical reduction method according to any one of the above items 1 to 5, in an XPS spectrum of the catalyst measured by X-ray photoelectron spectroscopy (XPS), there may be a peak between 457 eV and 460 eV, and the half width of the peak between 457 eV and 460 eV may be 1.1 eV to 1.5 eV.
[0018] ( 11 The catalyst according to one embodiment of the present invention comprises an oxide containing Ti, Isolated in the Ti-containing oxide Contains Cu.
[0019] ( 12 )the above( 11 The catalyst described in ) may have a content of the oxide containing Ti of 10 wt % or more.
[0020] ( 13 )the above( 11 )or( 12 In the catalyst described in ), at least a part of the oxide containing Ti may have a band gap of 3 eV or less.
[0021] ( 14 )the above( 11 )~( 13 In the catalyst described in any one of items (1) to (5), the Cu content may be 0.001 wt % to 90 wt %.
[0022] ( 15 )the above( 11 )~( 14 In the catalyst according to any one of the above items (1) to (5), the oxide containing Ti may be TiO2.
[0023] ( 16 )the above( 11 )~( 15 The catalyst according to any one of the above items (1) to (5) has an intensity I at a wavelength of 400 nm in an ultraviolet-visible absorption spectrum of the catalyst. 400 and the intensity I at wavelength 600 nm 600 Comparison with I 400 / I 600 may be 0.5 to 3.
[0024] ( 17 )the above( 11 )~( 16 The catalyst according to any one of items (1) to (5) may have a peak between 528 eV and 532 eV in an XPS spectrum measured by X-ray photoelectron spectroscopy (XPS), and the half-value width of the peak between these may be 1.2 eV to 1.55 eV.
[0025] ( 18 )the above( 11 )~( 17 The catalyst according to any one of items (1) to (5) above may have a peak between 457 eV and 460 eV in an XPS spectrum measured by X-ray photoelectron spectroscopy (XPS), and the half width of the peak between 457 eV and 460 eV may be 1.1 eV to 1.5 eV.
[0026] ( 19 )the above( 11 )~( 18 The catalyst according to any one of items (1) to (5) above may have a peak between 931 eV and 933 eV in an XPS spectrum measured by X-ray photoelectron spectroscopy (XPS), and the half width of the peak between 931 eV and 933 eV may be 1.4 eV to 1.9 eV.
[0027] ( 20 In one embodiment of the present invention, a method for producing a catalyst includes mixing raw materials, placing the raw materials in a sealed container, heating the sealed container until the surface temperature reaches a heating temperature, maintaining the heating temperature for 10 minutes or more to produce a precursor, and calcining the produced precursor at a calcination temperature for 1 minute or more to produce a catalyst, the raw materials including a titanium raw material and a copper raw material. When the precursor is fired, 2 The concentration is 0.5 vol% or more. .
[0028] ( 21 )the above( 20 In the method for producing a catalyst described in ), the titanium raw material may be titanium (IV) tetrabutoxide.
[0029] ( 22 )the above( 20 )or( 21 In the method for producing a catalyst described in ), the copper raw material may be copper (II) acetate.
[0030] ( 23 )the above( 20 )~( 22 In the method for producing a catalyst described in any one of ), the heating temperature may be 60°C to 280°C.
[0031] ( 24 )the above( 20 )~( 23 In the method for producing a catalyst according to any one of the above items 1 to 8, the calcination temperature may be 100°C to 800°C.
[0032] ( 25 )the above( 20 )~( 24In the method for producing a catalyst described in any one of the above items (1) to (5), a weight ratio (Ti:Cu) of titanium contained in the titanium raw material and Cu contained in the copper raw material in the sealed container may be 1:99 to 99.99:0.01.
[0033] ( 26 )the above( 20 )~( 25 In the method for producing a catalyst according to any one of the above items (1) to (5), the precursor may be calcined in an air atmosphere.
[0035] ( 27 )the above One of (20) to (26) In the method for producing a catalyst described in the above, the H2 concentration may be 100 vol% when the precursor is calcined. (28) An electrochemical reduction method according to one embodiment of the present invention is a method for reducing an oxide containing Ti by adding a solution having a pH of 5 to 15 and CO 2 and in a state where the CO 2 is electrochemically reduced, the catalyst contains Cu, and an XPS spectrum of the catalyst measured by X-ray photoelectron spectroscopy (XPS) has a peak between 931 eV and 933 eV, and the half-width of the peak between 931 eV and 933 eV is 1.4 eV to 1.9 eV. (29) An electrochemical reduction method according to one embodiment of the present invention is a method for reducing an oxide containing Ti by adding a solution having a pH of 5 to 15 and CO 2 and in a state where the CO 2 is electrochemically reduced, and the intensity I at a wavelength of 400 nm in the ultraviolet-visible absorption spectrum of the catalyst is 400 and the intensity I at wavelength 600 nm 600 Comparison with I 400 / I 600 is 0.5 to 3. Effect of the Invention
[0036] According to the above aspect of the present invention, there is provided an electrochemical reduction method in which the selectivity of CH4 production is improved in the electrochemical reduction reaction of CO2. and catalyst can be provided. [Brief description of the drawings]
[0037] [Figure 1] FIG. 1 is a schematic diagram of an electrochemical reduction device according to an embodiment. [Diagram 2] FIG. 1 is a diagram showing the relationship between the starting composition of a catalyst and the composition ratio of Cu measured by EDS. [Diagram 3] These are XRD patterns of the catalyst obtained by heat treatment in air, anatase TiO2, and brookite TiO2. [Figure 4] XRD patterns of the catalysts obtained by heat treatment under a hydrogen atmosphere, anatase TiO2, brookite TiO2, and Cu. [Diagram 5] These are O1sXPS spectra of catalysts obtained by heat treatment in air or hydrogen atmosphere with different Cu contents. [Figure 6] These are Ti2p3 / 2XPS spectra of catalysts obtained by heat treatment in air or hydrogen atmosphere with different Cu contents. [Figure 7] These are Cu2p3 / 2XPS spectra of catalysts obtained by heat treatment in air or hydrogen atmosphere with different Cu contents. [Figure 8] These are ultraviolet-visible absorption (UV-Vis) spectra of catalysts obtained by heat treatment in air with different Cu contents. [Figure 9] These are ultraviolet and visible absorption spectra of catalysts obtained by heat treatment under a hydrogen atmosphere with different Cu contents. [Figure 10] These are ultraviolet and visible absorption spectra of a catalyst prepared by treating TiO2-air with hydrogen and a sample catalyst prepared by reoxidizing the same. [Figure 11] This shows XPS spectra of C1S of catalysts obtained by heat treatment in air or hydrogen atmosphere with different Cu contents. [Figure 12] FIG. 1 shows the relationship between the starting Cu composition of the catalyst and the CK line intensity measured by EDS. [Figure 13] These are high-angle dark-field scanning transmission electron microscope images of catalysts obtained by heat treatment under a hydrogen atmosphere with different Cu contents. [Figure 14] FIG. 1 shows the relationship between Cu content and partial current density for methane production. [Figure 15] FIG. 1 shows the relationship between products and current density for 5Cu-TiO2-H and 50 wt% Nafion® catalysts. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0038] <Electrochemical reduction device> An electrochemical reduction device 100 used in an electrochemical reduction method according to an embodiment will be described below with reference to the drawings. The drawings used in the following description may show characteristic parts in an enlarged scale for the sake of convenience in order to make the characteristics easier to understand, and the dimensional ratios of each component may differ from the actual ones. The materials, dimensions, etc. exemplified in the following description are merely examples, and the present invention is not limited thereto, and may be modified as appropriate within the scope of the effects of the present invention.
[0039] FIG. 1 is a schematic diagram of an electrochemical reduction device 100 according to this embodiment. The electrochemical reduction device 100 includes an anode 10, a separator 15, a cathode 20, and a power source 140. The power source 140 is electrically connected to the anode 10 and the cathode 20. The electrochemical reduction device 100 of this embodiment further includes a first flow path plate 30, a second flow path plate 31, a third flow path plate 32, a fourth flow path plate 33, a first flow path structure 50, a second flow path structure 60, and a third flow path structure 70. The electrochemical reduction device 100 of this embodiment further includes a first solution delivery section 151, a waste liquid recovery section 152, a second solution delivery section 161, a liquid product recovery section 162, a gas delivery section 171, and a gas product recovery section 172. Each section will be described below.
[0040] (anode) The anode 10 is disposed between the first flow path plate 30 and the gas exhaust member 40. The anode 10 oxidizes a first electrolytic solution (described later) that flows into the anode chamber 53 from the first inlet 51 to generate oxygen, hydrogen ions, and the like. Of the products generated by oxidizing the first electrolytic solution, substances dissolved in the first electrolytic solution are discharged through the first outlet 52. Furthermore, gaseous products, such as O2, are discharged from the anode 10 through the opening 41 of the gas exhaust member 40. The anode 10 is, for example, a porous material. The material of the anode 10 is, for example, a metal such as nickel, titanium, or iron, or an alloy containing these metals. A specific example of the anode 10 is nickel foam.
[0041] The anode 10 may include a catalyst (oxidation catalyst) that promotes the oxidation of the first electrolytic solution. Examples of the oxidation catalyst include platinum, iridium, cobalt, and iron.
[0042] (Gas exhaust components) In the electrochemical reduction device 100, the gas exhaust member 40 is disposed between the anode 10 and the cover member 45. A separate flow path plate or the like may be disposed between the anode 10 and the gas exhaust member 40. The gas exhaust member 40 may include an opening 41 for discharging a gaseous product generated by the oxidation reaction of the anode 10. The gas exhaust member 40 does not have to include the opening 41. The gaseous product (oxygen) generated by the oxidation reaction occurring on the anode 10 is discharged from the opening 41 or the first outlet 52 together with the electrolytic solution.
[0043] (Covering material) In the electrochemical reduction device 100 , the cover member 45 is disposed in contact with the gas exhaust member 40 .
[0044] (First flow path plate) The first flow path plate 30 is disposed between the first flow path structure 50 and the anode 10. The first flow path plate 30 is provided with an opening 30a so that the first electrolytic solution and the anode 10 can come into contact with each other. The material of the first flow path plate 30 is not particularly limited as long as it is chemically stable and has insulating properties. Examples of the material of the first flow path plate 30 include polyether ether ketone (PEEK), fluororesin, and glass.
[0045] (First flow path structure 50) In the electrochemical reduction device 100, the first flow path structure 50 is disposed between the first flow path plate 30 and the second flow path plate 31, or between the first flow path plate 30 and the separator 15. The first flow path structure 50 includes a first inlet 51, a first outlet 52, an anode chamber 53, and a flow path 54. The first flow path structure 50 includes an opening 50a for contacting the anode 10 with the first electrolytic solution. The first flow path structure 50 also includes an opening 50b for contacting the separator 15 with the first electrolytic solution.
[0046] The first electrolytic solution is sent from first solution sending unit 151 to first inlet 51. The first electrolytic solution that has entered first inlet 51 enters flow path 54 and is sent to anode chamber 53. In anode chamber 53, an oxidation reaction of anode 10 progresses, and the first electrolytic solution after the reaction is discharged from first outlet 52 to waste liquid recovery unit 152. First solution sending unit 151 is composed of, for example, a tank and a pump that store the first electrolytic solution, a flow rate control unit that controls the flow rate, and the like.
[0047] (Second flow path plate) The second flow path plate 31 is disposed between the separator 15 and the first flow path structure 50. The material of the second flow path plate 31 is not particularly limited as long as it is chemically stable and has insulating properties. Examples of the material of the second flow path plate 31 include polyether ether ketone (PEEK), fluororesin, and glass. The second flow path plate 31 has an opening 31a that brings the separator 15 into contact with the first electrolytic solution. The electrochemical reduction device 100 can function without attaching the second flow path plate 31, but it is desirable to install it in order to easily prevent liquid leakage.
[0048] (Separator) The separator 15 is disposed between the anode 10 and the cathode 20. In this embodiment, the separator 15 is disposed between the second flow path plate 31 and the third flow path plate 32. The separator 15 can separate the anode 10 and the cathode 20 and can move some ions between the anode 10 and the cathode 20. The separator 15 is not particularly limited as long as it can separate the anode 10 and the cathode 20 and can move some ions between the anode 10 and the cathode 20. For example, the separator 15 is an ion exchange membrane. For example, the ion exchange membrane is a Nafion (registered trademark) membrane, which is a copolymer of fluororesin based on sulfonated tetrafluoroethylene, or a Sustainion (registered trademark) X37-50 Grade RT Membrane, which is a copolymer of styrene and vinylbenzyl chloride functionalized with 1-methylimidazole.
[0049] (Third flow plate) The third flow path plate 32 is disposed between the separator 15 and the second flow path structure 60. The material of the third flow path plate 32 is not particularly limited as long as it is chemically stable and has insulating properties. Examples of the material of the third flow path plate 32 include polyether ether ketone (PEEK), fluororesin, and glass. The third flow path plate 32 has an opening 32a that brings the separator 15 into contact with the first electrolytic solution. The electrochemical reduction device 100 can function without attaching the third flow path plate 32, but it is desirable to install the third flow path plate 32 in order to easily prevent liquid leakage.
[0050] (Second flow path structure) The second flow path structure 60 is disposed between the third flow path plate 32 and the fourth flow path plate 33, or between the separator 15 and the fourth flow path plate 33. The second flow path structure 60 includes a second inlet 61, a second outlet 62, a cathode chamber 63, and a flow path 64. A second electrolytic solution, which will be described later, flows through the flow path 64. The second flow path structure 60 includes an opening 60a for contacting the separator 15 with the second electrolytic solution. The second flow path structure 60 also includes an opening 60b for contacting the cathode 20 with the second electrolytic solution.
[0051] The second electrolytic solution is sent from the second solution sending section 161 to the second inlet 61. The second electrolytic solution that has entered the second inlet 61 enters the flow path 64 and is sent to the cathode chamber 63. In the cathode chamber 63, the reduction reaction of the cathode 20 progresses, and the second electrolytic solution containing the product generated by the reduction reactivity of the cathode 20 is discharged from the second outlet 62. The discharged second electrolytic solution is sent to the liquid product recovery section 162. In the liquid product recovery section 162, the product generated by the reduction reaction of the cathode 20 is recovered. The second solution sending section 161 is composed of, for example, a tank and a pump that store the second electrolytic solution, a flow rate control section that controls the flow rate, and the like.
[0052] (Fourth flow path plate 33) The fourth flow path plate 33 is disposed between the cathode 20 and the second flow path structure 60. The material of the fourth flow path plate 33 is not particularly limited as long as it is chemically stable and has insulating properties. Examples of the material of the fourth flow path plate 33 include polyether ether ketone (PEEK), fluororesin, and glass. The fourth flow path plate 33 has an opening 33a that brings the cathode 20 into contact with the second electrolytic solution.
[0053] (Cathode) The cathode 20 is disposed between the third flow path structure 70 and the fourth flow path plate 33. The cathode 20 includes a substrate 21 and a catalyst layer 22.
[0054] The substrate 21 has electrical conductivity and a function of transmitting the CO2-containing gas described later sent from the third flow path structure 70. The substrate 21 is preferably porous. Examples of the substrate 21 include carbon paper and carbon cloth.
[0055] The catalyst layer 22 is provided on the substrate 21 and is in contact with the second electrolytic solution. In the catalyst layer 22, a reduction reaction of CO2 is carried out using the ions supplied from the anode 10 and the CO2-containing gas supplied from the third flow path structure 70. The reduction reaction of CO2 occurs near the boundary between the substrate 21 and the catalyst layer 22, and gaseous products such as methane are discharged from the third outlet 72, and products dissolved in the second electrolytic solution are discharged from the second outlet 62.
[0056] The catalyst layer 22 contains a catalyst. The catalyst content is preferably 1 wt% or more with respect to the total mass of the catalyst layer 22. More preferably, the catalyst content is 10 wt% or more. Even more preferably, the catalyst content is 50 wt% or more. The catalyst content is preferably 99 wt% or less. More preferably, the catalyst content is 80 wt% or less.
[0057] The catalyst in the catalyst layer 22 contains an oxide containing Ti. By containing an oxide containing Ti, the selectivity for methane production can be improved.
[0058] The oxide containing Ti in the catalyst is preferably TiO2. TiO2 is a compound that exhibits chemical interaction with hydrogen. TiO2 absorbs visible light when reacted with hydrogen gas, so the conductivity of the catalyst can be improved by heat treatment under a hydrogen atmosphere.
[0059] The content of the oxide containing Ti is preferably 2 wt% or more based on the total mass of the catalyst. More preferably, the content of the oxide containing Ti is 5 wt% or more. Even more preferably, the content of the oxide containing Ti is 10 wt% or more. Particularly preferably, the content of the oxide containing Ti is 90 wt% or more. Since Cu does not need to be contained, the upper limit of the content of the oxide containing Ti may be 100 wt%. The content of the oxide containing Ti is preferably 99.999 wt% or less.
[0060] At least a part of the oxide containing Ti preferably has a band gap of 3 eV or less, and more preferably has a band gap of 2.5 eV or less.
[0061] The method for measuring the band gap of at least a part of the oxide containing Ti is explained below. Here, the ultraviolet and visible spectrum of the catalyst is measured, and the band gap value of the catalyst obtained from the spectrum obtained is regarded as the band gap value of at least a part of the oxide containing Ti. The band gap of the catalyst was calculated using Tauc plot. The Tauc plot is based on equation (2) proposed by Tauc, Davis, Mott et al., in which the absorption coefficient α in equation (1) is replaced with the value F(R∞) on the vertical axis of the spectrum after Kubelka-Munk transformation. (hνα) 1 / n =A(hν-Eg) (1) (hνF(R∞)) 1 / n =A(hν-Eg) (2) Here, h is the Planck constant, ν is the frequency, α is the absorption coefficient, Eg is the band gap, and A is the proportionality constant. n is determined by the type of transition of the sample, with n=1 / 2 for direct allowed transitions, n=3 / 2 for direct forbidden transitions, n=2 for indirect allowed transitions, and n=3 for indirect forbidden transitions. Since anatase TiO2 is an indirect transition semiconductor, n=1 / 2 is used. Based on the spectrum after Kubelka-Munk transformation, the horizontal axis is hν and the vertical axis is hνF(R∞) 1 / 2 On the graph of (hν,hνF(R∞)) 1 / 2 ) is plotted, the absorption curve near the absorption edge becomes linear, and by drawing a tangent line to this area and finding the point where it intersects with the horizontal axis, the band gap can be calculated.
[0062] The catalyst preferably further contains Cu. By containing Cu, the selectivity of methane production can be improved. The Cu content is preferably 0.001 wt% or more with respect to the total mass of the catalyst. More preferably, the Cu content is 1 wt% or more. Even more preferably, the Cu content is 3 wt% or more. The Cu content is preferably 90 wt% or less. More preferably, the Cu content is 20 wt% or less. Even more preferably, the Cu content is 10 wt% or less. Particularly preferably, the Cu content is 7 wt% or less.
[0063] In the UV-visible absorption spectrum of the catalyst, the intensity I at a wavelength of 400 nm 400 and the intensity I at wavelength 600 nm 600 Comparison with I 400 / I 600 It is preferable that the ratio I is 0.5 to 3. 400 / I 600 When the lattice constant is 0.5 to 3, hydrogen is incorporated into the lattice near the surface of TiO2. The presence of hydrogen near the surface of TiO2 allows hydrogen to be efficiently supplied from the TiO2 interface during the reduction reaction occurring on Cu. This can further improve the selectivity of methane production.
[0064] Ratio I 400 / I 600can be measured by the following method. Measure the UV-Vis absorption spectrum of the catalyst. The UV-Vis absorption spectrum is converted by the Kubelka-Munk function to obtain the intensity I at a wavelength of 400 nm. 400 and the intensity I at wavelength 600 nm 600 Tokara I 400 / I 600 Calculate.
[0065] In the spectrum (hereinafter sometimes referred to as XPS spectrum) measured by X-ray photoelectron spectroscopy (XPS), there is a peak (O1s peak attributed to O1s) between 528 eV and 532 eV, and the half-width of the peak between 528 eV and 532 eV is preferably 1.2 eV to 1.55 eV. The half-width refers to the full width at half maximum (FWHM). This makes it possible to prevent the catalyst from deteriorating due to the generation of oxygen vacancy sites. It is also found that new hydrogen sites are formed in the TiO2 lattice without generating oxygen vacancy sites. In this way, the introduction of hydrogen sites creates a new state inside the band, and therefore the conductivity can be improved by reducing the band gap of the oxide containing Ti on the catalyst surface. It also functions as a hydrogen source in the hydrogenation of the introduced CO2. This makes it possible to improve the speed of the reduction reaction.
[0066] In the XPS spectrum of the catalyst, a peak (Ti2p 3 / 2 Ti2p belonging to 3 / 2 It is desirable that the half-width of the peak between 457 eV and 460 eV be 1.1 eV to 1.5 eV even after hydrogen treatment. The peak with a top of 458.6 eV is Ti. 4+ The peak is between 457 eV and 460 eV, and the half-width of the peak is 1.1 eV to 1.5 eV, which means that no oxygen defects are generated. This improves the conductivity and increases the speed of the reduction reaction, even if no oxygen defect sites that cause deterioration are generated.
[0067] In the XPS spectrum of the catalyst, it is preferable that a peak is present between 931 eV and 933 eV, and the half width of the peak between 931 eV and 933 eV is 1.4 eV to 1.9 eV. 0 Here, the presence of a peak between 931 eV and 933 eV means that the peak top (the value at which the intensity is maximum) is between 931 eV and 933 eV. The same applies to other peaks. When there is a peak between 931 eV and 933 eV and the half-width of the peak is 1.4 eV to 1.9 eV, it is believed that Cu on the catalyst surface is Cu. 0 This improves the activity of the catalyst.
[0068] The XPS spectrum of the catalyst is measured as follows. The sample is placed on a spot with a size of 100 μm, with 10 times of accumulation (O1s, Ti2P 3 / 2 10 times, Cu2p 3 / 2 The half-width was calculated by fitting with a mixed function of Gaussian and Lorentzian functions.
[0069] The catalyst layer 22 may further contain a binder. The binder is not particularly limited, but is preferably, for example, an electrolyte polymer. An example of the electrolyte polymer is Nafion (registered trademark), which is a copolymer of fluororesin based on sulfonated tetrafluoroethylene. The content of the binder is, for example, 10 wt% to 50 wt%.
[0070] The catalyst layer 22 may further contain a conductive assistant such as acetylene black or carbon nanotubes.
[0071] (Third flow path structure) The third flow path structure 70 is disposed in contact with the substrate 21 of the cathode 20. The third flow path structure 70 is in contact with the surface of the substrate 21 opposite to the surface on which the catalyst layer 22 is provided. The third flow path structure 70 includes a third inlet 71, a third outlet 72, a gas chamber 73, and a gas flow path 74. A CO2-containing gas described below flows through the gas flow path 74. The third flow path structure 70 includes an opening 70a for contacting the cathode 20 with the CO2-containing gas.
[0072] The CO2-containing gas is sent from the gas delivery section 171 to the third inlet 71. The CO2-containing gas that has entered the third inlet 71 enters the gas flow passage 74 and is sent to the gas chamber 73. In the gas chamber 73, the reduction reaction of the cathode 20 progresses, and the CO2-containing gas that contains the gas product generated by the reduction reaction of the cathode 20 (hereinafter, may be referred to as the product gas) is sent from the third outlet 72 to the gas product recovery section 172.
[0073] The electrochemical reduction device 100 according to this embodiment has been described in detail above. According to the electrochemical reduction device 100 according to this embodiment, it is possible to improve the selectivity of methane production in the reduction reaction of CO2.
[0074] Although a reference electrode is not provided in the electrochemical reduction device 100 of this embodiment, a reference electrode may be provided. An example of the reference electrode is a mercury-mercury oxide electrode (Hg / HgO).
[0075] In the electrochemical reduction device 100 of this embodiment, the first flow path plate 30, the second flow path plate 31, the third flow path plate 32, and the fourth flow path plate 33 are used, but each of the flow path plates may not be used.
[0076] Although the gas exhaust member 40 is provided with the opening 41, the opening 41 may be omitted if gaseous substances such as O2 produced by the oxidation reaction at the anode 10 can be removed.
[0077] <Electrochemical reduction method> Next, the electrochemical reduction method according to the present embodiment will be described. In the electrochemical reduction method according to the present embodiment, CO2 is electrochemically reduced in a state where a solution having a pH of 5 to 15 and CO2 are brought into contact with a catalyst containing an oxide containing Ti. Hereinafter, a method for performing the electrochemical reduction method using the electrochemical reduction device 100 will be described, but the present invention is not limited to the method using the electrochemical reduction device 100.
[0078] The electrochemical reduction method according to this embodiment includes a first electrolytic solution delivery step of delivering a first electrolytic solution to the anode chamber 53, a second electrolytic solution delivery step of delivering a second electrolytic solution to the cathode chamber 63, a CO2-containing gas delivery step of delivering a CO2-containing gas to the gas chamber 73, and an electrochemical reduction step of electrochemically reducing CO2. In this embodiment, each step is carried out, for example, in parallel.
[0079] (First electrolyte delivery process) In the first electrolytic solution delivery step, the first electrolytic solution is delivered from first solution delivery section 151 to anode chamber 53. In addition, a product of the oxidation reaction occurring in anode 10 is delivered to waste liquid recovery section 152.
[0080] The first electrolytic solution is an electrolytic solution containing at least water (H2O). For example, the first electrolytic solution may be an electrolytic solution containing at least one selected from the group consisting of hydroxide ions, potassium ions, hydrogen ions, sodium ions, lithium ions, chloride ions, sulfate ions, carbonate ions, and nitrate ions. Examples of the electrolyte include potassium hydroxide and sodium hydroxide.
[0081] The pH of the first electrolytic solution is 5 to 15. The pH of the first electrolytic solution is preferably equal to or higher than 6. When the pH of the first electrolytic solution is 5 to 15, the oxidation reaction at the anode 10 can proceed more easily.
[0082] The flow rate of the first electrolytic solution can be set appropriately depending on the area of anode 10 and the volume of anode chamber 53.
[0083] (Second electrolyte delivery process) In the second electrolytic solution delivery step, the second electrolytic solution is delivered from the second solution delivery section 161 to the cathode chamber 63. In addition, a product resulting from the reduction reaction occurring in the cathode chamber 63 is delivered to the liquid product recovery section 162.
[0084] The second electrolytic solution is an electrolytic solution containing at least water. For example, the second electrolytic solution may be an electrolytic solution containing at least one selected from the group consisting of hydroxide ions, potassium ions, hydrogen ions, sodium ions, lithium ions, chloride ions, sulfate ions, carbonate ions, and nitrate ions. Examples of the electrolyte include potassium hydroxide and sodium hydroxide.
[0085] The second electrolytic solution has a pH of 5 to 15. The second electrolytic solution preferably has a pH of 6 or higher. When the first electrolytic solution has a pH of 5 to 15, the oxidation reaction at the anode 10 can proceed more easily. The first and second electrolytic solutions preferably have the same pH.
[0086] The flow rate of the second electrolytic solution can be appropriately set according to the area of the cathode 20 and the volume of the cathode chamber 63. The flow rate of the second electrolytic solution is 0.5 ml min -1 ~7ml min -1 It is.
[0087] (CO2-containing gas delivery process) In the CO2-containing gas delivery process, the CO2-containing gas is delivered from the gas delivery section 171 to the gas chamber 73. In addition, a gaseous product (gaseous product) resulting from the reduction reaction occurring in the cathode chamber 63 is delivered to the gaseous product recovery section 172.
[0088] The CO2 concentration in the CO2-containing gas is preferably 10 vol% or more based on the total volume of the CO2-containing gas. More preferably, the CO2 concentration in the CO2-containing gas is 50 vol% or more. Even more preferably, the CO2 concentration in the CO2-containing gas is 90 vol% or more. The upper limit of the CO2 concentration is 100 vol%.
[0089] The flow rate of the CO2-containing gas can be appropriately set according to the area of the cathode 20 and the volume of the cathode chamber 63. The flow rate of the CO2-containing gas is, for example, 1 to 15 sccm.
[0090] (Electrochemical reduction process) In the electrochemical reduction process, CO2 is electrochemically reduced. Specifically, a voltage is applied between the anode 10 and the cathode 20 from the power source 140 to supply a current. When a current is passed between the anode 10 and the cathode 20, an oxidation reaction proceeds near the anode 10, and a reduction reaction proceeds near the cathode 20. In the following reaction, methane (CH4) is used as an example, but in the electrochemical reduction process, other substances such as C2H4 and CO may also be produced. The reaction between the anode 10 and the cathode 20 will be described separately.
[0091] When a current is supplied between the anode 10 and the cathode 20 from the power source 140, a water oxidation reaction occurs between the anode 10 and the first electrolytic solution in contact with the anode 10. Specifically, when the pH is 7 or less, the water contained in the first electrolytic solution is oxidized to generate oxygen and hydrogen ions, as shown in the following formula (3). 2H2O→4H + +O2+4e - (3) When the pH is greater than 7, the OH contained in the first electrolyte solution is depleted as shown in the following formula (4). - is oxidized to produce oxygen and water. 4OH - →O2+2H2O+4e ― (4)
[0092] When the pH is below 7, H generated at anode 10 + The current (e - ) and H that has reached the catalyst layer 22 of the cathode 20 +As a result, an electrochemical reduction reaction of CO2 proceeds. Specifically, as shown in the following formula (5), CO2 in the CO2-containing gas supplied from the gas chamber 73 to the cathode 20 is reduced to CH4. That is, CH4 is generated by electrochemically reducing CO2. CO2+8H + +8e - →CH4+2H2O···(5) When the pH is greater than 7, CO2 contained in the first electrolyte is reduced and reacts with H2O to form CH4 and OH, as shown in the following formula (6). - The generated OH - is transported through the separator to the anode. CO2+6H2O+8e - →CH4+8OH - (6)
[0093] The reaction at the cathode 20 described above proceeds on the catalyst of the catalyst layer 22. That is, when the catalyst of the catalyst layer 22 is brought into contact with a solution of pH 5 to 15 and CO2, the CO2 is electrochemically reduced.
[0094] The voltage applied between the anode 10 and the cathode 20 is, for example, 0 V to −4.0 V. More preferably, the voltage is −1.0 V to −2.5 V. If the voltage is −1.0 V to −2.5 V, the electrochemical reduction reaction of CO2 can proceed with higher energy conversion efficiency.
[0095] The electrochemical reduction method according to the present embodiment has been described above. According to the electrochemical reduction method of the present embodiment, the selectivity of CH4 production can be improved in the electrochemical reduction method of CO2.
[0096] <Catalyst manufacturing method> Next, the method for producing the catalyst according to this embodiment will be described. In the method for producing the catalyst according to this embodiment, the raw materials are mixed and placed in a sealed container, and the sealed container is heated until the surface temperature reaches a heating temperature, and then the heating temperature is maintained for 10 minutes or more to produce a precursor, and the precursor thus produced is calcined at a calcination temperature for 1 minute or more to produce a catalyst. In this embodiment, a catalyst is produced using a solvothermal method. The method for producing the catalyst according to this embodiment will be described below.
[0097] (raw materials) In the method for producing a catalyst according to this embodiment, the raw materials include a titanium raw material containing titanium (Ti) and a copper raw material containing copper (Cu).
[0098] Examples of the titanium raw material include titanium (IV) methoxide, titanium (IV) tetrabutoxide, titanium (IV) isopropoxide, titanium diboride, etc. As the titanium raw material, titanium (IV) tetrabutoxide is preferred.
[0099] The copper source is, for example, copper(II) acetate, copper(II) stearate, or copper(II) chloride. The copper source is preferably copper(II) acetate.
[0100] The weight ratio (Ti:Cu) of titanium (Ti) contained in the titanium raw material and copper (Cu) contained in the copper raw material is preferably 1:99 to 99.99:0.01. More preferably, the weight ratio (Ti:Cu) is 10:90 to 99:1. Even more preferably, the weight ratio (Ti:Cu) is 50:50 to 93:7. If the weight ratio (Ti:Cu) is 99:1 to 90:10, Cu can be effectively isolated in the oxide containing Ti, but CH4 can be generated if Cu can be isolated at any other weight ratio. If the Cu atom is not isolated, the proportion of C2 compounds generated by the C-C bond of two COs increases. The isolation of Cu can improve the selectivity of methane generation.
[0101] The heating temperature of the closed container is preferably 60° C. to 280° C. If the temperature is within the range of 60° C. to 280° C., the catalyst precursor can be produced in high yield. The heating temperature is more preferably 180° C. to 220° C.
[0102] The retention time after the heating temperature of the closed container is reached is preferably 10 minutes or more. More preferably, the retention time is 1 hour or more. By making the retention time 10 minutes or more, the yield of the catalyst precursor can be increased.
[0103] The calcination temperature of the precursor is preferably 100° C. to 800° C. When the calcination temperature is in the range of 100° C. to 800° C., a catalyst can be produced from the precursor. The calcination temperature is more preferably 300° C. to 500° C.
[0104] The atmosphere in which the precursor is calcined is not particularly limited. The atmosphere in which the precursor is calcined may be air or a hydrogen atmosphere. In the method for producing a catalyst according to the present embodiment, calcination is preferably performed in a hydrogen atmosphere.
[0105] The H2 concentration during calcination of the precursor is preferably 0.5 vol% or more. More preferably, the H2 concentration during calcination is 5 vol% or more. More preferably, the H2 concentration during calcination is 99.9 vol% or more. The upper limit of the H2 concentration is 100 vol%. If the H2 concentration is 1 vol% or more, at least a part of the Cu in the catalyst can be replaced by Cu. 0 In addition, hydrogen can be incorporated into the lattice near the surface of TiO2, improving the selectivity of methane production.
[0106] <Cathode manufacturing method> The cathode 20 is obtained by forming a catalyst-containing catalyst layer 22 on a porous and conductive substrate 21. There is no particular limitation on the method for forming the catalyst layer 22. For example, the catalyst layer 22 may be formed on the substrate 21 by applying a dispersion liquid in which the catalyst is dispersed to the substrate 21 and drying the applied liquid.
[0107] The method of applying the dispersion liquid is not particularly limited. For example, the dispersion liquid (catalyst ink) may be applied using a spray. The dispersion liquid may contain a binder or the like.
[0108] The electrochemical reduction method, catalyst, and catalyst manufacturing method according to the present embodiment have been described above. The technical scope of the present invention is not limited to the above embodiment, and various modifications can be made without departing from the spirit of the present invention. In addition, the components in the above embodiment can be appropriately replaced with well-known components without departing from the spirit of the present invention. EXAMPLES
[0109] Next, an embodiment of the present invention will be described, but the conditions in the embodiment are merely an example of conditions adopted to confirm the feasibility and effects of the present invention, and the present invention is not limited to this example of conditions. Various conditions can be adopted in the present invention as long as they do not deviate from the gist of the present invention and the object of the present invention is achieved.
[0110] (Catalyst synthesis) Titanium(IV) tetrabutoxide was quickly added to a mixture of 30 mL of N,N-dimethylformamide (99.5%), 0.207 mL of 2-propanol, and copper(II) acetate, anhydrous. The PTFE container containing the mixture was transferred to a stainless steel autoclave, sealed, and placed in an oven at 200 °C for 20 h. The solid obtained was centrifuged at 7500 rpm for 10 min. The resulting precursor was separated and then washed several times with ethanol, acetone, and hexane. The precursor was then dried under vacuum at room temperature. Finally, the precursor was centrifuged in air or hydrogen flow (60 ml min -1) at 450℃ for 30 minutes (heat treatment) to obtain catalyst (xCu-TiO2-y). The x in xCu-TiO2-y indicates the amount of Cu doped in the catalyst (x wt.%). The y in xCu-TiO2-y indicates the atmosphere during heating. Here, y=air when heated in air, and y=H when heated in H2 atmosphere. 1mL of titanium(IV) tetrabutoxide was quickly added to a mixture of 30mL of N,N-dimethylformamide (99.5%), 0.215mL of 2-propanol, and an amount of copper(II) acetate (anhydrous) equivalent to the desired loading amount. 6.64mg of copper(II) acetate (anhydrous) was used to prepare 1Cu-TiO2. Similarly, TiO2-y was obtained by synthesizing under the same conditions as xCu-TiO2-y, except that copper(II) acetate was not added. The y in TiO2-y indicates the atmosphere during heating. Here, when heating in air, y = air, and when heating in H2 atmosphere, y = H. The weight ratio (Ti:Cu) of titanium (Ti) in titanium (IV) tetrabutoxide and copper (Cu) in copper acetate was adjusted to a range of 100:0 to 90.5:9.5.
[0111] (Elemental composition of catalyst) The elemental compositions of the prepared catalysts were measured by energy dispersive X-ray spectroscopy (EDS) using a JED-2300 (JEOL).
[0112] (XRD pattern of catalyst) Powder X-ray diffraction (XRD) patterns of the catalysts were obtained at the RIKEN Materials Science Beamline BL44B2.
[0113] (UV-Visible absorption spectrum) The UV-Vis absorption spectra of the catalysts were measured using a V-670 (JASCO). The reflection intensities in the UV-Vis absorption spectra were converted to intensities corresponding to the optical absorption coefficients using the Kubelka-Munk function.
[0114] (XPS) X-ray photoelectron spectroscopy (XPS) spectra of the catalysts were measured using Al Kα radiation with a VersaProbeII (ULVAC-PHI). The binding energies of the XPS spectra were corrected by setting the C1s binding energy of the carbon atom of the ligand in the sample at 284.5 eV.
[0115] (STEM) Scanning transmission electron microscopy (STEM) of the catalysts was performed using a JEM-ARM200F (JEOL) at 200 kV.
[0116] (Preparation of electrodes) A gas diffusion electrode (GDE) for the cathode was prepared by the following method. Carbon paper (Fuel Cell Store Sigracet 22 BB with a microporous layer) was used as the substrate. 200 μL of 2-propanol, 200 μL of water, 10 μL of Nafion® solution (Sigma-Aldrich 527084), and 1 mg of the catalyst powder synthesized above were mixed. The mixture was placed in a 4 mL screw vial and ultrasonically dispersed for 15 minutes to prepare a catalyst ink. The obtained catalyst ink was sprayed onto carbon paper with an airbrush to prepare a cathode.
[0117] (Electrochemical CO2 reduction reaction) The electrochemical CO2 reduction reaction (ECO2R) was carried out using a three-electrode electrochemical reduction device, which was equipped with a reference electrode (mercury-mercury oxide electrode (Hg / HgO)) in addition to the electrochemical reduction device shown in Figure 1. The cathode manufactured by the above method was used, and nickel foam was used as the anode. The electrode area of the cathode in the electrochemical reduction device was 1 cm2. 2 A Nafion (registered trademark) 117 cation exchange membrane was used to separate the cathode and anode compartments.
[0118] A 1M KOH solution (pH 13.8) was pumped into the cathode chamber at a rate of 7 mL min -1 , 1 mL min in the anode chamber -1 Pure CO2 gas was introduced into the gas chamber of the electrochemical reduction device 100 at a rate of 15 mL min-1 The cathode potential was converted to the reversible hydrogen electrode (RHE) value using the following equation (7). All voltages shown here are without iR correction. E(vs.RHE)=E(vs.Hg / HgO)+0.098V+0.0591V×pH...(7)
[0119] (Analysis of products in electrochemical CO2 reduction reaction) The gas products generated during the electrochemical CO2 reduction reaction were analyzed using a micro GC (Inficon Micro GC Fusion (registered trademark)) equipped with a Molsieve 5A column and a Plot Q column coupled with a thermal conductivity detector (TCD).
[0120] The liquid products produced by the electrochemical CO2 reduction reaction were analyzed by a high-performance liquid chromatograph (HPLC, LC-20AD, Shimadzu) equipped with a refractive index detector (RID-10A, Shimadzu).
[0121] The Faraday efficiency (FE) of the product is defined by the following formula (8): i is the number of moles of product i, z in equation (8) i represents the number of electrons required to produce product i. CO, formic acid, and H2 are z i =2, CH4 is z i = 8. C2H4 is z i = 12, C2H6 is z i = 14. F in formula (8) is the Faraday constant (96,485 C mol -1 ) In equation (8), Q is the amount of charge that flows into ECO2R.
[0122]
number
[0123] In the case of gaseous products, n i was calculated based on the following formula (9), where xi is the volume fraction of gas product i, P0 is the atmospheric pressure (1 atm), and ν is the flow rate of CO2 (0.015 L min -1 ), t is the reaction time, and R is the gas constant (0.08205 L atm mol -1 K -1 ), and T is 298 K.
[0124]
number
[0125] (Catalyst element ratio) Figure 2 shows the relationship between the starting Cu composition for the obtained xCu-TiO2 sample and the elemental composition determined by EDS measurement. The horizontal axis of Figure 2 represents the Cu content (wt%) at the start of synthesis, and the vertical axis of Figure 2 represents the Cu content (wt%) in the catalyst after synthesis. As shown in Figure 2, the elemental composition determined by EDS measurement is in good agreement with the starting composition ratio, and it was confirmed that roughly the desired amount of Cu was contained.
[0126] (Catalyst structure) Figure 3 shows the XRD patterns of the catalyst (xCu-TiO2-air), anatase TiO2, and brookite TiO2 obtained by heat treatment in air. The horizontal axis of Figure 3 is 2θ (degrees), and the vertical axis is intensity (au). Figure 4 shows the XRD patterns of the catalyst (xCu-TiO2-air), anatase TiO2, brookite TiO2, and Cu obtained by heat treatment in a hydrogen atmosphere. The horizontal axis of Figure 4 is 2θ (degrees), and the vertical axis is intensity (au).
[0127] As shown in Figures 3 and 4, in the catalysts obtained by heat treatment in air or in a hydrogen atmosphere, diffraction lines from anatase TiO2 and a small amount of brookite TiO2 were observed. As shown in Figure 4, in the Cu-TiO2-H obtained by heating in a hydrogen atmosphere, diffraction from Cu was observed in catalysts with a Cu content of 5 wt% or more. In other words, it was revealed that Cu nanoparticles are present in catalysts containing 5 wt% or more of Cu.
[0128] 6-coordinate Ti 4+ ion (0.605 Å) and Cu 2+ (0.73 Å) is different from Cu. 2+ The diffraction peak position of anatase was larger in the case of TiO2, but no shift in the diffraction peak position was observed in any of the catalysts, suggesting that most of the Cu introduced into the catalysts was not doped into the TiO2 lattice but was dispersed near the TiO2 surface.
[0129] (XPS spectrum of catalyst) Figure 5 shows the XPS spectrum of O1s of catalysts obtained by heat treatment under air or hydrogen atmosphere with different Cu contents. As shown in Figure 5, a peak was confirmed between 528 eV and 532 eV (O1s peak). Figure 5 shows the XPS spectrum of O1s of TiO2 (TiO2) with Cu0 wt%, 1Cu-TiO2 with Cu1 wt%, 3Cu-TiO2 with Cu3 wt%, 5Cu-TiO2 with Cu5 wt%, 7Cu-TiO2 with Cu7 wt%, and 10Cu-TiO2 with Cu10 wt%. The solid line of each XPS spectrum indicates that the catalyst was heat treated under hydrogen atmosphere (H2), and the dashed line of each XPS spectrum indicates that the catalyst was heat treated under air (air). The horizontal axis in Figure 5 indicates the binding energy (eV), and the vertical axis indicates the normalized intensity (au). In addition, fitting was performed on the obtained O1s peak to obtain the full width at half maximum (FWHM) (unit: eV). The results are shown in Table 1. As shown in Figure 5 and Table 1, the XPS spectra of O1s were almost the same except for 10Cu-TiO2-air and 10Cu-TiO2-H2. This indicates that the O atoms near the surface of xCu-TiO2-y have a similar bonding environment regardless of the heat treatment atmosphere or Cu content. The difference in the spectrum of 10Cu-TiO2-air is thought to be due to Cu(II) species. In other words, it was revealed that there are no oxygen defects on the surfaces of Cu-TiO2-air and Cu-TiO2-H.
[0130] [Table 1]
[0131] Figure 6 shows the Ti2p of the catalysts obtained by heat treatment in air or hydrogen atmosphere with different Cu contents. 3 / 2 As shown in Figure 6, the XPS spectrum has a peak between 457 eV and 460 eV (Ti2p 3 / 2 Figure 6 shows the Ti2p peaks of TiO2 (TiO2) with 0 wt% Cu, 1Cu-TiO2 with 1 wt% Cu added, 3Cu-TiO2 with 3 wt% Cu added, 5Cu-TiO2 with 5 wt% Cu added, 7Cu-TiO2 with 7 wt% Cu added, and 10Cu-TiO2 with 10 wt% Cu added. 3 / 2 6 shows XPS spectra. The solid line in each XPS spectrum indicates that the heat treatment was performed in a hydrogen atmosphere (H2), and the dashed line in each XPS spectrum indicates that the heat treatment was performed in air (air). The horizontal axis in FIG. 6 shows the binding energy (eV), and the vertical axis shows the normalized intensity (au). The obtained Ti2p 3 / 2 The peak was fitted and the obtained Ti2p 3 / 2 The full width at half maximum (FWHM) of the peak (unit: eV) was obtained, and the results are shown in Table 2.
[0132] [Table 2]
[0133] Ti 2p in xCu-TiO2-y in Figure 6 3 / 2 As shown in the XPS spectra, both the catalysts heat-treated in air or hydrogen atmosphere had Ti. 4+ This is a typical TiO2-based TiO2-based symmetric peak at 458.6 eV. 4+ The spectrum shape of the -O bond is shown. No clear peak shift to the lower energy side was observed between the catalysts. Therefore, regardless of the heat treatment atmosphere or the difference in Cu content, Ti near the surface of xCu-TiO2-y is Ti 4+This confirmed that no oxygen defects were introduced. In addition, as shown in Table 2, the full width at half maximum tended to be smaller when hydrogen treatment was performed.
[0134] Figure 7 shows the Cu2p of catalysts obtained by heat treatment in air or hydrogen atmosphere with different Cu contents. 3 / 2 The XPS spectrum is shown in FIG. 7. As shown in FIG. 7, a peak was confirmed between 931 eV and 933 eV (Cu2p 3 / 2 Peak) Figure 7 shows the Cu2p of 1Cu-TiO2 with 1wt% Cu added, 3Cu-TiO2 with 3wt% Cu added, 5Cu-TiO2 with 5wt% Cu added, 7Cu-TiO2 with 7wt% Cu added, and 10Cu-TiO2 with 10wt% Cu added. 3 / 2 7 shows XPS spectra. The solid line in each XPS spectrum indicates that the heat treatment was performed in a hydrogen atmosphere (H2), and the dashed line in each XPS spectrum indicates that the heat treatment was performed in air (air). The horizontal axis in FIG. 7 shows the binding energy (eV), and the vertical axis shows the normalized intensity (au). The obtained Cu2p 3 / 2 The peak was fitted and the obtained Cu2p 3 / 2 The full width at half maximum (FWHM) of the peak (unit: eV) was obtained, and the results are shown in Table 3.
[0135] [Table 3]
[0136] In the spectrum of Cu-TiO2-air in Figure 7, the Cu2p 3 / 2 The peak at 933.6 eV and the shoulder peak on the high binding energy side were assigned to Cu(I) and Cu(II), respectively. In xCu-TiO2-air, it was found that Cu(I) and Cu(II) were mainly present on the TiO2 surface as oxides. As shown in Table 3, the full width at half maximum of Cu-TiO2-air tended to be wider than that of the hydrogen-treated case. In Table 3, "-" indicates that Cu2p 3 / 2 This indicates that no peak was identified.
[0137] In the spectrum of xCu-TiO2-H in Fig. 7, the Cu2p 3 / 2 This peak was determined by the Cu 0 In other words, in xCu-TiO2-H, the main 0 It was found that these exist on the TiO2 surface as
[0138] (UV-Visible absorption spectrum of catalyst) Figure 8 shows the UV-visible absorption spectra of catalysts obtained by heat treatment in air with different Cu contents. The horizontal axis of Figure 8 is the wavelength (nm), and the vertical axis corresponds to the light absorption coefficient, which is the Kubelka-Munk transformation of the reflectance R (au).
[0139] As shown in Figure 8, TiO2-air is a white powder and shows strong absorption in the ultraviolet region. The band gap of the catalyst was calculated using the Tauc plot. The Tauc plot is based on the above formula (2) proposed by Tauc, Davis, Mott et al., where the absorption coefficient α in the above formula (1) is replaced with the value F(R∞) on the vertical axis of the spectrum after Kubelka-Munk transformation. Here, h is the Planck constant, ν is the frequency, α is the absorption coefficient, Eg is the band gap, and A is the proportionality constant. n is determined by the type of transition of the sample, and n=1 / 2 for direct allowed transitions, n=3 / 2 for direct forbidden transitions, n=2 for indirect allowed transitions, and n=3 for indirect forbidden transitions. Since anatase TiO2 is an indirect transition semiconductor, n=1 / 2 is used. Based on the spectrum after Kubelka-Munk transformation, the horizontal axis is hν and the vertical axis is hνF(R∞) 1 / 2 On the graph of (hν,hνF(R∞)) 1 / 2 ) is plotted, the absorption curve near the absorption edge becomes linear, and the band gap can be calculated by drawing a tangent line to this area and finding the intersection point with the horizontal axis. The band gap values of each catalyst calculated using the Tauc plot are shown in Table 4. They are smaller than the band gap (3.24 eV) of the Catalysis Society's reference catalyst JRC-TIO-7 (anatase titanium oxide).
[0140] [Table 4] In the Cu-doped catalyst xCu-TiO2-air, the absorption peak shifted slightly to the visible region with increasing Cu content, and absorption bands appeared between 400nm-500nm and 550nm-1500nm. The first absorption band between 400nm-500nm is attributed to the interfacial charge transfer from the O2p orbital forming the valence band of TiO2 to the Cu(II) state attached to TiO2, and the absorption band between 550nm-1500nm is attributed to the dd transition of Cu(II). These results indicate that Cu on xCu-TiO2-air exists as Cu(II), similar to the XPS results.
[0141] Figure 9 shows the ultraviolet-visible absorption spectra of catalysts obtained by heat treatment under a hydrogen atmosphere with different Cu contents. The horizontal axis of Figure 9 is the wavelength (nm), and the vertical axis corresponds to the optical absorption coefficient, which is the Kubelka-Munk transformation of the reflectance R (au). TiO2-H and 1Cu-TiO2-H obtained by heat treatment under a hydrogen atmosphere are dark brown powders, and show a unique absorption not observed in white TiO2 from 400 nm to the near infrared region. The ratio I of the intensity at 400 nm to the intensity at a wavelength of 600 nm obtained from Figures 8 and 9 is 400 / I 600 The ratio I of the catalyst heat-treated under hydrogen atmosphere is shown in Table 5. 400 / I 600 tended to be lower than those obtained when heat treatment was performed in air.
[0142] [Table 5]
[0143] To understand the origin of the change in optical properties in TiO2-H2, we measured the UV-visible absorption spectra of a sample of TiO2-air treated with hydrogen and a sample that was reoxidized (Fig. 10). The horizontal axis of Fig. 10 is the wavelength (nm), and the vertical axis corresponds to the optical absorption coefficient, which is the Kubelka-Munk transformation of the reflectance R (au). TiO2-air-H2 in Fig. 10 shows the catalyst obtained by heating TiO2-air at 450°C for 30 minutes in a hydrogen atmosphere, and TiO2-air-H-air shows the catalyst obtained by heating TiO2-air-H2 again at 450°C for 30 minutes in air. TiO2-air-H, obtained by hydrogen treatment of white TiO2-air, was dark brown like TiO2-H and showed absorption in the visible to near infrared region. Furthermore, sample TiO2-air-H-air, obtained by heating TiO2-air-H again in air, showed a white color and a spectrum similar to TiO2-air, and showed no absorption in the visible to near infrared region. Therefore, it was suggested that the unique absorption observed in the absorption spectra of TiO2-H and 1Cu-TiO2-H was caused by the incorporation of hydrogen into the lattice near the TiO2 surface.
[0144] (C1s XPS spectrum) C-doped TiO2 also shows absorption in the visible to near infrared region. Figure 11 shows the results of C 1s XPS measurement of xCu-TiO2-air and xCu-TiO2-H for the purpose of detecting carbon derived from organic titanium raw materials that may have been doped into the TiO2 lattice. The doped carbon shows a peak at about 281.8 eV that is attributed to carbon ions, which is different from the peak at 284.6 eV (CC) binding energy of the main peak of C1s derived from impurities. As shown in Figure 11, xCu-TiO2-air and xCu-TiO2-H do not have a carbon ion peak (281.8 eV), and no noticeable difference was observed between the catalysts. Therefore, it was confirmed that the absorption in the visible region observed in the UV-visible absorption spectrum of xCu-TiO2-H is not derived from doped carbon.
[0145] In addition, SEM-EDS analysis showed no significant difference in the intensity of the CK lines detected in xCu-TiO2-air and xCu-TiO2-H (Fig. 12), confirming that the visible absorption observed in the UV-visible absorption spectrum of xCu-TiO2-H is not due to impurity carbon. In 3Cu-TiO2-H, which contains 3 wt% or more Cu obtained by heat treatment in a hydrogen atmosphere, an absorption band due to Cu surface plasmon (SPR) appeared at 575 nm to 580 nm. As shown by the results of XRD and XPS, it was found that Cu nanoparticles were formed on these catalysts.
[0146] (Electron microscope image) The high-angle dark-field scanning transmission electron microscope images obtained by heat treatment under a hydrogen atmosphere with different Cu contents are shown in Figure 13. The high-angle dark-field scanning transmission electron microscope (HAADF-STEM) images confirmed that Cu species were highly dispersed.
[0147] (catalytic activity) Figure 14 shows the relationship between the Cu content and the partial current density for methane production. The horizontal axis of Figure 14 shows the Cu content (wt%), and the vertical axis shows the partial current density for methane production (mA cm -2 ) CH4 was produced even without Cu, but the partial current density for CH4 production was greatly improved by supporting Cu. In particular, the hydrogen-treated catalyst xCu-TiO2-H showed a dramatic increase in current density compared to xCu-TiO2-air. It is believed that the activity of the catalyst was increased by the Cu content and heat treatment under a hydrogen atmosphere.
[0148] The relationship between product distribution and current density when ECO2R was performed using the 5Cu-TiO2-H catalyst is shown in Figure 15. The horizontal axis of Figure 15 is the current density (mA cm -2 ), the first vertical axis indicates the Faraday efficiency (%), and the second vertical axis indicates the IR free voltage (V vs RHE). As shown in Figure 15, when the 5Cu-TiO2-H catalyst was used, the selectivity to CH4 in the CO2 reduction product was 90%. From the above, it was found that the catalyst disclosed herein can selectively reduce CO2 to CH4. The faradaic efficiency to CH4 was 50%, and the partial current density for CH4 production was 100 mA cm -2 It was. [Industrial Applicability]
[0149] INDUSTRIAL APPLICABILITY The electrochemical reduction method, catalyst, and catalyst manufacturing method disclosed herein can improve the selectivity for CH4 production in the electrochemical reduction reaction of CO2, and therefore have high industrial applicability. [Explanation of symbols]
[0150] 10 anode, 15 separator, 20 cathode, 30 first flow path plate, 31 second flow path plate, 32 third flow path plate, 33 fourth flow path plate, 40 gas exhaust member, 45 Lid member, 50 first flow path structure, 60 second flow path structure, 70 third flow path structure, 100 electrochemical reduction device, 140 power supply, 151 first solution delivery section, 152 waste liquid recovery section, 161 second solution delivery section, 162 liquid product recovery section, 171 gas delivery section, 172 gas product recovery section
Claims
1. A catalyst containing an oxide containing Ti and Cu, and having an XPS spectrum measured by X-ray photoelectron spectroscopy (XPS) with a peak between 931 eV and 933 eV and a half-width of the peak between 1.4 eV and 1.9 eV, A solution of pH 5 to 15 and CO 2 With the and in contact, The CO 2 is electrochemically reduced, The electrochemical reduction method, wherein at least a part of the oxide containing Ti has a band gap of 3 eV or less.
2. A catalyst for electrochemical reduction of CO 2 comprising an oxide containing Ti and Cu dispersed in isolation near the surface of the Ti-containing oxide, wherein an XPS spectrum measured by X-ray photoelectron spectroscopy (XPS) has a peak between 931 eV and 933 eV and a half-width of the peak is 1.4 eV to 1.9 eV.
3. A catalyst containing an oxide containing Ti, A solution having a pH of 5 to 15 is contacted with CO 2 , Electrochemically reducing the CO 2 ; The catalyst contains Cu, In the electrochemical reduction method, in an XPS spectrum of the catalyst measured by X-ray photoelectron spectroscopy (XPS), there is a peak between 931 eV and 933 eV, and the half-width of the peak is 1.4 eV to 1.9 eV.
Citation Information
Patent Citations
A Cu-doped TiO2 coupled semiconductor photocatalyst, its preparation method, and its application.
CN102274729A
Preparation method of load bimetal type Cu-Pt / TiO2-NBs catalyst and application
CN104549368A
Copper-based water gas shift catalyst, preparation method and application thereof
CN110508282A
Carbon dioxide reducing electrode and carbon dioxide converter
JP1995188961A
Electrocatalyst for electrochemical conversion of carbon dioxide
US20130256124A1
